2011
DOI: 10.1177/014556131109001010
|View full text |Cite
|
Sign up to set email alerts
|

Lateral pharyngeal diverticulum: A report of 3 cases

Abstract: Pharyngocele, or lateral pharyngeal diverticulum (LPD), is rare, as only a few cases have been described. Th is condition is characterized by local bulging in the piriform recess or in a vallecula. Th e diagnosis, which is clinically diffi cult, is made by barium-swallow examination of the pharynx. Surgical repair is indicated when symptoms are present. We report 3 new cases of LPD, and we discuss the etiology and clinical features of this entity. We also present a short review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(40 citation statements)
references
References 15 publications
0
40
0
Order By: Relevance
“…[6] Most of the cases in the series were unilateral; also, in their short series in the year 2011, Brazilian authors Porcaro-Salles et al reported three cases of unilateral pharyngocele. [7] Bilateral cases are also reported; Martinez et al present a case of a 71-year-old male with chance discovery of bilateral pharyngoceles. [8] The diagnosis, which may be clinically difficult, can be made with varied radiological and ultrasonographic techniques, though clinical examination may be satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Most of the cases in the series were unilateral; also, in their short series in the year 2011, Brazilian authors Porcaro-Salles et al reported three cases of unilateral pharyngocele. [7] Bilateral cases are also reported; Martinez et al present a case of a 71-year-old male with chance discovery of bilateral pharyngoceles. [8] The diagnosis, which may be clinically difficult, can be made with varied radiological and ultrasonographic techniques, though clinical examination may be satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] Other authors suggest that this anomaly may represent a third or fourth branchial cleft anomaly. Most authors posit that increased intraluminal pressure causes inherent weak areas of the pharynx, the areas between the overlapping constrictor muscles, to bulge outward.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12][13][14][15] This description fails to address intraluminal anatomy or some of the important surrounding structures, including the thyroid cartilage and superior laryngeal neurovascular bundle. [3][4][5][6][7][8][9][10][11][12][13][14][15] This description fails to address intraluminal anatomy or some of the important surrounding structures, including the thyroid cartilage and superior laryngeal neurovascular bundle.…”
Section: Discussionmentioning
confidence: 99%
“…Diverticula are uncommon in the EI, and they generally are of 4 types: lateral pharyngeal or laryngopharyngeal diverticulum, [31][32][33][34] Zenker's diverticulum, 35 diverticulum or pseudodiverticulum, 40 and KillianJamieson diverticulum 41-43 (Video 2, available online at www.giejournal.org). Diverticula in the EI and esophagus are best studied by barium esophagram.…”
Section: Diverticulamentioning
confidence: 99%
“…The treatment is surgical or endoscopic. [33][34] Zenker's diverticulum is the protrusion of pharyngeal mucosa through the posterior wall of the pharynx through the Killian triangle, limited inferiorly by the cricopharyngeal muscle and laterally by the thyropharyngeal muscle (Fig. 13).…”
Section: Diverticulamentioning
confidence: 99%